Rok 1989 z perspektywy przedstawicieli klasy politycznej - Karkowska, Marta (Kultura i Społeczeństwo, 2021)
This article is an attempt to reconstruct the perceptions of 1989 of members of parliament who had a key influence on the systemic changes. The author traces the similarities, differences, and transformations of their narratives on this subject. The article is based on interviews conducted as part of two studies (the first was conducted in 1994–1995, the second in 2018–2020) with the same seven leading Polish politicians from the ruling and opposition political groups. The author describes both studies, with an explanation of the methodology and an analysis of the collected material. Both are presented from the perspective of a researcher belonging to this generation of sociologists, for whom the materials from the first study have become mainly a historical source and were the basis for the work involved in the second research project. The analysis focuses on the similarities and differences in interpreting themes at two points in time, for instance, perceptions of 1989, descriptions of the political elite and its relationship with society, and ways of presenting the phenomena generally referred to as “the transformation.”